Addressing challenges and charting future directions in tuberculosis control - Majani Edward; Ameh Wisdom Owoicho (Discover Public Health)
Abstract Tuberculosis (TB) remains a major global health challenge, affecting millions annually. Despite significant progress in screening and treatment efforts, substantial hurdles persist, hindering the global aspiration for TB eradication. This article delves into the critical challenges that continue to impede progress in TB control and provide the recommendation for future direction. These challenges include persistent diagnostic complexities, particularly for difficult-to-diagnose forms like pediatric and extrapulmonary TB (including central nervous system TB), the alarming rise and spread of drug-resistant TB (MDR-TB and XDR-TB), the pervasive impact of social stigma on care-seeking and adherence, and the long-term disruptions caused by the COVID-19 pandemic on TB services. To overcome these multifaceted obstacles, we propose strategic directions for future research and development. These emphasize the urgent need for innovative, sensitive, and accessible diagnostic tools (including AI-based and CRISPR/Cas assays), the development and widespread deployment of highly effective TB vaccines (such as M72/AS01E and MTBVAC), and comprehensive strategies to combat drug resistance (including shorter, all-oral regimens like BPaL/BPaLM). We also highlight the importance of strengthening healthcare systems, leveraging digital health, and fostering community engagement to reduce stigma and improve patient outcomes. Tuberculosis remains a significant global health burden, demanding sustained and intensified efforts. Addressing these challenges requires a multi-faceted approach encompassing the development of innovative tools, the implementation of effective prevention and treatment strategies, and a resolute commitment to tackling the social determinants of TB. By focusing on these outlined future directions, the global community can strive towards reducing the burden of this devastating disease and ultimately achieve a TB-free world, underpinned by robust global funding and unwavering political will.